Investigation of selective laser melting process for Cu-5Sn alloy on surface roughness, microstructure and mechanical property. Issue 1 (3rd August 2021) - Yang, Peng; He, Dingyong; Wang, Zengjie; Tan, Zhen; Fu, Hanguang; Shao, Wei; Guo, Xingye
Abstract : Purpose: In this research, the highly dense bulk Cu-5Sn alloy specimens were fabricated using selective laser melting (SLM). This study aims to establish the relationship between laser power (LP), scanning speed (SS) and hatch space (HS) with surface roughness (Ra) and density. To obtain Cu-5Sn alloy formed parts with high strength and low surface roughness. The microstructure and mechanical properties of SLMed Cu-5Sn were investigated. Design/methodology/approach: The relative density (RD) was optimized using the response surface method (RSM) and analysis of variance. First, the Ra of SLMed formed specimens was studied to optimize the forming process parameters with a good surface. Then, the dense specimens were studied by ANOVA and the RSM to obtain dense specimens for mechanical property analysis. Findings: Dense specimens were obtained by RSM and ANOVA. The tensile properties were compared with the casted specimens. The yield and ultimate strengths increased from 71 and 131 MPa for the cast specimens to 334 and 489 MPa for the SLMed specimens, respectively. The ductility increased significantly from 11% to 23%, due to the refined microstructure of the SLMed specimens, as well as the formation of many twin crystals. Originality/value: The Ra, RD and mechanical properties of SLM specimens Cu-5Sn were systematically studied, and the influencing factors were analyzed together. This study provides a theoretical and practical example to improve the surface quality and RD.